Quality Control standardization of Wild Himalayan Pear: Pyrus pashia - Hemalatha, Siva; Sharma, Priyanka; Prasad, Satyendra Kuldip (EManuscript Services, 2016)
Introduction: To establish the pharmacognostical and phytochemical standardization parameters of Pyrus pashia fruits in order to ensure quality and safety of this traditionally acclaimed medicinal tree. Methods: The fresh fruits of P. pashia were collected and dried. Fruit was subjected to various pharmacognostical investigations, Extraction procedures, and preliminary phytochemical screening, according to WHO guidelines. Ethanolic extract was standardized to total phenolic and flavonoid content, followed by phytochemical quantification of P. pashia extract using lupeol as a chemical marker by HPLC method. Results: In the present study, microscopy of the fruit showed typical characteristics of berry, having thick fleshy pericarp differentiated into thin epicarp and thick mesocarp having wide radiating carpel chambers with one or two seeds attached in axile placentum. Further, physicochemical evaluation was done like, loss on drying, total ash value, acid insoluble ash value, water soluble ash value, fluorescence analysis etc. Heavy metal and pesticide residue analysis was also performed. Furthermore, ethanolic extract of Pyrus pashia (EPP) obtained from cold maceration and phytochemical screening of different fractions obtained by liquid partitioning revealed the presence of various secondary metabolites such as glycosides, steroids, triterpenoids, phenols flavonoids etc. Moreover, the total phenolic content and total analysis revealed that fruits are rich source of phenols and flavonoid. The HPLC chromatogram suggested that EPP contained 4.24% w/w of lupeol. Conclusion: Pharmacognostical and phytochemical investigation will ensure quality and safety of this medicinal plant, furthermore HPLC quantification will aid in authentication and development of monograph.
Keywords: HPLC; Lupeol; Pyrus pashia; Standardization; Total flavonoid content; Total phenolic content